Characterization of Boron Doped 316L Powder Metallurgy (PM) Stainless Steel - Uzunsoy, Deniz; Yeprem, H. Aygul (CARL HANSER VERLAG, 2008)
Powder Metallurgy (PM) is a shaping technology which is based on forming powder particles in a mold under high pressure. This method influences cost of parts significantly due to direct molding. Sintering is one of the most critical steps of a PM process. Mechanical and physical properties of the final product are enhanced by the optimisation of sintering conditions (temperature, time, and type of the atmosphere). The demand for PM products with high performance is increasing day by day. In this context, one way to increase the strength of the part is to perform sintering process by alloying powder. Boron was found to be useful for the activation of sintering process of iron powder in the previous study. In recent times, research is increasingly focused on the Boron addition to improve the density of PM stainless steel parts after sintering process. In this study, the influence of Boron addition into PM 316L stainless steel materials on the microstructure and properties of the final part has been investigated in detail. Boron addition is varied from 0.2 to 1 wt.-%, and the effect of Boron on the densification and distortion behaviour of stainless steel has also been studied. All samples are characterised by using several techniques such as SEM, EDX, image analysis.
Keywords: ADDITIONS; Materials Science